Applying a developmental perspective to aquatics and swimming - Langendorfer, S. J. (Biomechanics and Medicine in Swimming XI, 2010)
Most typically in the aquatic field instructors and coaches employ an "error correction model" to view all swimming behaviors. Using a "straw person" approach, clinicians expect all learners regardless of age or skill to swim like an elite adult swimmer. In this approach errors are corrected mainly when external experts such as teachers or coaches expunge those errors using command style direct teaching. In command teaching, a coach verbally describes and then demonstrates the expected"expert" way of swimming followed by identifying the "errors" the learner makes that deviate from the expert model. In contrast, a "developmental perspective" is defined as a view in which one expects and anticipates regular, ordered changes to occur in swimming behaviors across the entire lifespan. From a developmental perspective, changes in swimming behavior occur as a result of systemic interactions among individual, task, and environmental characteristics as proposed by Newell (1986). For example, this view expects that someone learning to swim on the front gradually and systematically will change the arm, leg, and breathing patterns they use to move through the water because their body size or density changes, or the way they interact with the task is altered. In this paper I provide a conceptual overview that compares and contrasts the developmental and error correction approaches in swimming by drawing upon contemporary thinking in dynamical systems and motor development theory. In particular, I highlight the three essential clinical skills that aquatic clinicians need to possess when using "developmentally appropriate practices" (DAP) (i.e., developmental assessment, individualization of instruction, and developmental task analysis). For each DAP clinical skill, I provide practical illustrations for how these DAP skills apply to learning in aquatics and swimming. I argue that the predominance of the error correction model within swimming and aquatics has severely limited the field`s acceptance and use of best instructional, learning, and assessment practices as well as unnecessarily constrained thinking about swimming skill acquisition in ways that acceptance of a developmental perspective would remedy.